A cooperação internacional do Instituto de Ciências Matemáticas e de Computação da Universidade de São Paulo (ICMC-USP), de 2010 a 2014 - Ferreira, Luana Rufino (Universidade Federal de São Carlos, 2016)
This research had the purpose of conducting a data survey of international cooperation practiced by the Institute of Mathematics and Computer Science of Universidade de São Paulo, in the 2010-2014 period. Were recovered and mapped the data of international cooperation related to the following modalities: scientific production with researchers from foreign institutions; international cooperation agreements and memorandum of understanding (formal agreements); missions of foreign university professors for academic activities at ICMC-USP; missions of ICMC-USP professors for academic activities abroad foreign delegations visits at ICMC-USP (professors or staff); ICMC-USP delegations abroad (professors or staff); ICMC-USP´s undergraduate students in student exchange program; ICMC-USP´s graduate students in exchange abroad; undergraduate students from foreign institutions in exchange at ICMC-USP; graduate students from foreign institutions in exchange at ICMC-USP; foreign students enrolled in undergraduate courses at ICMC-USP (full course);Foreign students enrolled in graduate programs at ICMC-USP (full course);foreign postdocs at ICMC-USP with the purpose of analyzing how was carried out international cooperation in the ICMC. After the inventory of data, parameters were built to supply a future database of various modalities of international cooperation of the institute as a public management tool of international cooperation, in that institute.
Keywords: International Cooperation; ICMC; USP; Cooperação internacional; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA